(untitled) (ENTHYMEMA, 2020)
This work aims to propose a hypothesis of lecture of Alessandro De Francesco’s La visione a distanza (Arcipelago Itaca, 2018) and starting from this analysis it would suggest some critical reflections about several textual practices developed in the last two decades within the framework of italian experimental poetry, or the so-called ‘poesia di ricerca’. In the last De Francesco’s collection of poems, which contains both edited and unedited texts, one of the most relevant phenomena could be the highly evident complexity on a stylistic, graphic and typographic level. On the other hand, we can find a common trace which places these texts on an intermedial dimension, not exclusively verbal, related to a complex aesthetical phenomenology in the domain of visual arts, performance arts and installations.